An exploratory study of loading and morphometric factors associated with specific failure modes in fatigue testing of lumbar motion segments - Sean Gallagher; William S. Marras; Alan S. Litsky; Deborah Burr (The National Institute for Occupational Safety and Health (NIOSH))
Background. There is currently little information regarding factors associated with specific modes of motion segment failure using a fatigue failure model. Methods. Thirty-six human lumbar motion segments were fatigue tested using spinal compressive and shear loads that simulated lifting a 9 kg weight in three torso flexion angles (0, 22.5, and 45). Twenty-five segments failed via fatigue prior to the 10,000 cycle maximum. These specimens were visually inspected and dissected so that the mode(s) of failure could be determined.Failure modes included endplate fractures (classified into nine varieties), vertebral body fractures, and/or zygapophysial joint disruption. Logistic regression analyses were performed to determine whether certain morphometric variables, amount of motion segment flexion, disk degeneration scores, and/or loading characteristics were associated with the occurrence of specific failure modes. Findings. Results indicated that stellate endplate fractures were associated with increased posterior shear forces (P < 0.05) and less degenerated discs (P < 0.01). Fractures running laterally across the endplate were associated with motion segments having larger volumes (P < 0.01). Endplate depression was more common in smaller specimens (P < 0.01), as well as those experiencing increased posterior shear force (P < 0.05). Zygapophysial joint damage was more likely to occur in a neutral posture (P < 0.01).Interpretation. These results suggest that prediction of failure modes (e.g., specific endplate fracture patterns) may be possible (atleast for older specimens)